Ugoda zawarta przed mediatorem w postępowaniu karnym jako tytuł wykonawczy - Sławicki, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article presents the legal nature of mediation settlements in criminal proceed-ings. The ﬁ rst chapter describes the genesis of the provisions governing a mediation settlement. Subsequently, proceedings will be presented regarding the issue of a writ of enforcement. The last part will deal with the issue of the legal nature of a settlement in enforcement proceedings.
Keywords: mediacja; ugoda; tytuł egzekucyjny